Analysis Of Compensation Provisions In Improving Employee Performance (Case Study Of BPJS Ketenagakerjaan Sumedang) - Solihin Royani; Tuti Widiawati (Journal of Bussines Management Basic, 2023)
Human resources have an important role in an organization, they must havequality, innovative and creative human resources. Because the organization is a networkand decision successors of policy and decision making. Compensation is used as a measureof performance with the aim of getting qualified employees, retaining employees andmaking a good contribution to the organization. This research uses descriptive qualitative. The direct researcher acts as the main research tool in which the research process isdirectly and actively interviewing, collecting data, processing data, processing data/dataanalysis, reporting and drawing conclusions. The results showed that the provision of nonfinancial compensation in improving the performance of BPJS Ketenagakerjaan Sumedang employees can be said to be effective. It can be seen from several interviews, through nonfinancial compensation indicators, especially promotions, which are categorized as goodbut not perfect and employee performance indicators, especially quality and quantity, arecategorized as good but not perfect.